Analisis Kinerja Ruas Jalan Abdullah Silondae Kota Kendari (Studi Kasus : Pasar Korem Dan Mall Mandonga) - Hado Hado; Laode Muhammad Fahrizal Ahsan; Nur Alam Syah (Universitas Sulawesi Tenggara, 2026)
This study aims to analyze the characteristics and performance of traffic on Abdullah Silondae Street, Kendari City. The study results indicate that the highest traffic volume occurs on Saturdays, reaching 1,192 pcu/h in both directions, while the road capacity is recorded at 5,298 pcu/h. The number of observed side obstacles reached 2,159 incidents, categorized as very high. Road performance is indicated by a free-flow speed of 39.9 km/h and an average passenger vehicle speed of approximately 38 km/h, with a degree of saturation of 0.24. Based on these values, the road's level of service is category B, indicating stable traffic flow, although speed is starting to be affected by traffic conditions. This study recommends restructuring activities around the road, analyzing long-term traffic growth scenarios, and evaluating safety aspects and the use of other transportation modes. Further research is expected to formulate a more comprehensive traffic management strategy to improve road performance and safety.